Acquired 5-Fluorouracil Resistance in Human Pancreatic Carcinoma Cells. A Paradigm for Chemoresistance Mechanisms in Pancreatic Cancer - Schober, Marvin; Jesenofsky, Ralf; Faissner, Ralf; Krug, Sebastian; Weidenauer, Cornelius; Hagmann, Wolfgang; Haas, Stephan L; Heuchel, Rainer L; Löhr, Matthias J (JOP. Journal of the Pancreas, 2015)
Context Pancreatic ductal adenocarcinoma is a dismal disease with one of the worst prognoses amongst solid tumors. Its ability to develop chemoresistance mechanisms towards cytotoxic drugs is the main cause of treatment failure. Objective Here, we have established a drug-resistance model for pancreatic cancer in which Capan-1 pancreatic carcinoma cells (designated Capan-1 5-FU2000) acquired 5-fluorouracil (5-FU) resistance and were used as a paradigm to reveal alterations in intracellular signaling cascades that. Those alterations may contribute to the circumvention of apoptosis during the course of the disease, culminating in treatment failure. Methods We made use of 2-D-gelelectrophoresis, mass-spectrometry, sandwich-ELISA and western blotting to compare the proteomic expression patterns of respective mediators involved in pro- and antiapoptotic as well as inflammatory processes in both cell lines. An ATP-based chemosensitivity assay validated the chemoresistant phenotype of the Capan-1 5-FU2000 clones. Results We detected specific changes in our resistant cell clones in particular a decreased expression of S100A4. We also found a decreased basal phosphorylation of SAPK/JNK and P38. The expression of the pro-apoptotic mediators Bok and Bad was down- and up-regulated in these cells, respectively. In case of NfkB p65 and IkB-alpha treatment with 5-FU (2,000 µg/mL for 96 h) markedly induced phosphorylation in native Capan-1 cells. In contrast in resistant clones it decreased phosphorylation of NfkB p65 and did not affect IkB-alpha phosphorylation. Basal phosphorylation of S6-ribosomal-protein was markedly increased in resistant clones, treatment with 5-FU decreased this phosphorylation, while in native Capan-1 cells it was vice versa. Conclusion Thus we can conclude that several pathways were found to be altered in chemoresistant Capan-1 5-FU2000 cells. Moreover these alterations are most likely the consequence of a multistep adaption towards gradual cytotoxic exposure finally culminating in a chemoresistant phenotype. Interfering with these pathways may possibly reverse the phenotype and thus open up alternative treatment options. Image: Effect of 5-FU treatment on NfkB p65 phosphorylation in native and 5-FU resistant cells.